About artificial intelligence... - Sarwat Hussain (Journal of the Pakistan Medical Association, 2022)
Early computers were used as automatic calculation tools. Later, as the Industrial Revolution began, manufacturing devices, were developed to automate more complex tasks, such as guiding weaving patterns on looms. It was not until 1950s, that the Computer Science began to be established as a defined academic discipline. Early on, researchers realized that, based on the ability of the computer to process logic, it may be possible to programme computers to mimic mental capabilities generally associated with basic human intelligence and intellect. In 1956 this attribute was termed, Artificial Intelligence (AI) by John McCarthy, an American computer scientist.1 Nothing much happened for several decades. In 1997, computer science once again came in the lime light, when a massive worldwide media coverage was given to a computer, IBM Deep Blue beating the reigning world chess champion, Gary Kasparov. In a 6- game match the computer won 2-1 with three draws.2 A computer wining in a game, requiring intellect and analytic thinking, brought the world’s attention to the extraordinary capabilities of computers. Subsequent surge in investment in AI research surged and the convergence of the following three elements brought the AI to its current prominence: